The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1037/pha0000015
|View full text |Cite
|
Sign up to set email alerts
|

Delay discounting of food by rhesus monkeys: Cocaine and food choice in isomorphic and allomorphic situations.

Abstract: Research on delay discounting has focused largely on non-drug reinforcers in an isomorphic context in which choice is between alternatives that involve the same type of reinforcer. Less often, delay discounting has been studied with drug reinforcers in a more ecologically valid allomorphic context where choice is between alternatives involving different types of reinforcers. The present experiment is the first to examine discounting of drug and non-drug reinforcers in both isomorphic and allomorphic situations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 55 publications
(82 reference statements)
6
40
0
4
Order By: Relevance
“…Bickel et al (2011) found a trend for cocaine addicts to discount delayed money more when the alternative was immediate cocaine than when the alternative was immediate money. Huskinson et al (2015) found that rhesus monkeys discounted delayed food more steeply when the alternative was immediate cocaine than when the alternative was immediate food. These findings are consistent with the steep discounting of delayed food that we observed when the alternative to delayed food was immediate delivery of a 16 µg/kg/inj dose of remifentanil, and they are consistent with similar effects in rhesus monkeys (Maguire et al 2013).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Bickel et al (2011) found a trend for cocaine addicts to discount delayed money more when the alternative was immediate cocaine than when the alternative was immediate money. Huskinson et al (2015) found that rhesus monkeys discounted delayed food more steeply when the alternative was immediate cocaine than when the alternative was immediate food. These findings are consistent with the steep discounting of delayed food that we observed when the alternative to delayed food was immediate delivery of a 16 µg/kg/inj dose of remifentanil, and they are consistent with similar effects in rhesus monkeys (Maguire et al 2013).…”
Section: Discussionmentioning
confidence: 96%
“…Since the percent choice curve and the area under this curve could be affected by the nondelayed values of the drug and nondrug options, or by the difference between these two values, the shape of the curves obtained in these experiments might not generalize to other amounts of food. More complete information could be obtained by determining indifference points between delayed and nondelayed rewards over a wider range of values (Bickel et al 2011; Huskinson et al 2015; Mazur 1987). However, despite this limitation, the comparisons obtained with the streamlined procedure clearly demonstrate that the nature of the immediate drug option strongly affects the value of the delayed nondrug option.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the current findings with remifentanil, taken together with studies using cocaine, support the hypothesis that in nonhuman primates drug reinforcers in general might be discounted less steeply than non-drug reinforcers such as sweetened solutions (see Freeman et al, 2009; 2012). A recent study reported that the rate at which food is discounted depends upon whether food or drug (cocaine) is available as the immediately delivered alternative (Huskinson et al, 2015), demonstrating that the types of commodities that are available, as either the immediate or the delayed option, also impact discounting. It is not known whether monkeys in the current study might discount other opioids (e.g., heroin), drugs with different pharmacological mechanisms (e.g., cocaine), or non-drug reinforcers (e.g., food) at different rates.…”
Section: Discussionmentioning
confidence: 99%
“…Studies to date indicate that delaying delivery of an otherwise preferred reinforcer, whether food (Maguire et al, 2013b; Woolverton and Anderson, 2006; Huskinson et al 2015) or a dose of drug (Maguire et al, 2013a; Woolverton and Anderson, 2006; Woolverton et al, 2007), increases responding for a small and less preferred reinforcer (e.g., small dose of drug). Delaying presentation of preferred commodities increases the effectiveness of small immediately-available commodities.…”
Section: Discussionmentioning
confidence: 99%